Covid-19 Risk Factors and Radiographic Severity Index Description in Covid-19 Patients Dr. Mohammad Hoesin Palembang 2021 - Alfian Hasbi; Budi Santoso; Anjeli Primeisa (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: COVID-19 is a pandemic disease caused by droplet infection from SARS-CoV-2. Due to its rapidtransmission and high case fatality rate, the identification of risk factors and prognostic factors is important.Obesity is a risk factor for poor outcomes in COVID-19. It is associated with chronic inflammation, disorders of theimmune system. Obesity can be determined based on BMI. Chest X-Ray is supported in establishing the diagnosisand prognosis of COVID-19 patients. Assessment of the severity index of Chest X-Ray radiographs can use theModified Chest X-Ray Scoring System of RSUP Dr. Soetomo. This study was conducted to analyze the relationshipbetween BMI and chest radiography severity index in hospitalized COVID-19 patients at dr. Mohammad HoesinPalembang in 2021.Methods: This research used a cross-sectional analytic observational design. Sampling was done using aconsecutive sampling technique with 70 samples and obtained from the patient's medical record. The data wereanalyzed by univariate and bivariate (Chi-Square) using IBM SPSS Statistics 26 software.Results: Patients with BMI Overweight-Obesity had more in Moderate-Severe (18.6%) radiographic severityindex scores (18.6%) than Normal-Mild (15.7%). Chi-Square bivariate analysis, BMI (p=0.033; p-value <0.05) hada significant relationship with the chest radiographic severity index with Odds Ratio 3,00, 95% CI (1,073–8,386).Conclusion: There is a significant relationship between body mass index and chest radiography severity index inCOVID-19 patients. Overweight-Obesity BMI patients have a 3-fold chance of having a Moderate-Severe categoryof radiographic severity index compared to Underweight-Normal BMI patients.